2008
DOI: 10.1590/s0073-47212008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and genetic differentiation among populations of Eupemphix nattereri (Amphibia, Anura, Leiuperidae) from central Brazil

Abstract: To assess genetic structure and phenotypic diversity of Eupemphix nattereri Steindachner, 1863, morphometric and molecular analyses were carried out for nine populations from the State of Goiás. A total of 11 morphometric traits were evaluated and genetic information was estimated using RAPD markers. Genetic and phenotypic distances were determined as a function of geographical origin. Correlation among genetic, morphometric, micro, and macroenviromental were analyzed by the Mantel test. Genetic data indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
7
11
0
1
Order By: Relevance
“…The genetic structure of populations, caused by restricted gene flow, random genetic drift, new mutations and natural selection of subpopulations in different environments may be revealed as variations in color and local adaptations on morphological features that indicate populational divergences (SPREITZER et al, 2012). Besides, genetic and environmental differences can cause diversity in ontogenetic development, resulting in body size variation (SILVA et al, 2008). Even among populations subjected to slightly differentiated environmental conditions, morphological differences may occur as a result of evolutionary processes other than local selection.…”
Section: Final Considerationsmentioning
confidence: 99%
“…The genetic structure of populations, caused by restricted gene flow, random genetic drift, new mutations and natural selection of subpopulations in different environments may be revealed as variations in color and local adaptations on morphological features that indicate populational divergences (SPREITZER et al, 2012). Besides, genetic and environmental differences can cause diversity in ontogenetic development, resulting in body size variation (SILVA et al, 2008). Even among populations subjected to slightly differentiated environmental conditions, morphological differences may occur as a result of evolutionary processes other than local selection.…”
Section: Final Considerationsmentioning
confidence: 99%
“…The causes of morphological differences between populations are often quite difficult to explain (Poulet et al, 2004;Silva et al, 2008). It has been suggested that the morphological characteristics of fishes are determined by an interaction between genetic and environmental factors (Swain and Foote, 1999;Poulet et al, 2004;Salini et al, 2004;Pinheiro et al, 2005;AnvariFar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic variability may not necessarily reflect population differentiation at the molecular level (Silva et al, 2008). Thus, we supplemented our morphological results with those obtained by the RAPD technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La variación geográfica en las estructuras morfológicas, particularmente el tamaño corporal, es común en muchas especies (Schäuble 2004, Silva et al 2008. Entre los anuros, los análisis de variación geográfica intraespecífica en morfología han revelado una amplia variación en el tamaño del cuerpo Schäuble 2004).…”
Section: Discussionunclassified